2010
DOI: 10.1111/j.1753-0407.2009.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and incretin responsiveness improve glucose control independently after gastric bypass surgery

Abstract: IntroductionOne of the major benefits of gastric bypass (GBP) surgery is the remission of Type 2 diabetes in 60-80% of cases.1 The rapidity of onset and the magnitude of the effect of GBP on diabetes remain incompletely explained. In addition to the effect of caloric restriction and weight loss, gut peptides, such as incretins, may play a role in the metabolic improvement after GBP.2,3 The incretins glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) enhance pancreatic insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 25 publications
6
95
0
2
Order By: Relevance
“…43 Whether this is true in humans is unknown. It is legitimate to hypothesize that the chronic and sustained elevation of postprandial GLP-1 after RYGBP 28,44 could have a long-term trophic effect on the human β-cells in vivo; however, this is unknown. However, there is little evidence that chronic use of GLP-1 analogs, in patients with type 2 diabetes, restores and/or prevents the deterioration of β-cell function.…”
Section: Rygbp Alters Incretin Physiology Rygbp Enhances Incretin Relmentioning
confidence: 99%
“…43 Whether this is true in humans is unknown. It is legitimate to hypothesize that the chronic and sustained elevation of postprandial GLP-1 after RYGBP 28,44 could have a long-term trophic effect on the human β-cells in vivo; however, this is unknown. However, there is little evidence that chronic use of GLP-1 analogs, in patients with type 2 diabetes, restores and/or prevents the deterioration of β-cell function.…”
Section: Rygbp Alters Incretin Physiology Rygbp Enhances Incretin Relmentioning
confidence: 99%
“…In addition to the increase in incretins, adiponectin and leptin decrease due to weight loss after GBP, beta cell function improves and abnormally elevated proinsulin and amylin levels decrease in diabetic patients [21]. Moreover, more studies have shown changes in amino-acid metabolism after GBP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies and reports have shown that 5 -20 years after GBP, there was a significant rise in the GLP-1 and GIP postprandial levels compared to nonoperated individuals [11,19,20]. Incretin level and effect, early phase insulin release during the Oral Glucose Tolerance Test (OGTT) and the insulinogenic index all are corrected promptly after GBP, while fasting glucose, fasting insulin, leptin or adiponectin improve due to weight loss in the first year post GBP [21].…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the secretion of incretin hormones produced in the small intestine and their effects on insulin and glucagon production may be a mediator of the significant improvement in blood glucose levels after gastric bypass surgery, which would not show the same effects when compared to weight loss caused by diet or restrictive surgeries [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…These two incretins are responsible for approximately 50% of postprandial secretion of insulin 21,22 .…”
Section: Discussionmentioning
confidence: 99%